Karoo crossroads: The green frontier and the enduring fault line - Borchardt, Stephanie Paula (New Agenda: SA Journal of Social and Economic Policy, 2025)
Stellenbosch University’s DSTI/NRF SARChI Research Programme on the Sociology of Land, Environment and Sustainable Development exposes a fundamental contradiction in the resource-rich Karoo; global scientific, environmental, and financial development initiatives collide with local realities of inequality, dispossession, and ecological fragility. In this editorial, STEPHANIE PAULA BORCHARDT asks if the impoverished communities who live there have reason to celebrate? This special issue of New Agenda: South African Journal of Social and Economic Policy emerges from the work of the DSTI/NRF SARChIResearch Chair1 in the Sociology of Land, Environment and Sustainable Development at Stellenbosch University, and reflects the Chair’s central focus: to interrogate the meanings and practices of sustainable development in the Karoo, a region marked by environmental vulnerability, historical marginalisation, and speculative futures. The research looks beyond policy to examine how development is experienced, imagined, and contested on the ground. Drawing on sociological and anthropological approaches, the Chair seeks to build theory that is locally grounded, attentive to power and place, and responsive to the complexities of rural transformation.